Misconceptions about HIV infection and testing services: A qualitative pilot survey in Lagos. Issue 4 (1st October 2020) - Wright, Kikelomo O.; Dairo, Magbagbeola D.; Odugbemi, Babatunde A.; Adepoju, Funmilade O.; Adebayo, Bisola I.; Durojaiye, Temitope O.; Shogbamimu, Yeside O. A.; Odusanya, Olumuyiwa O.; Idris, Olajide
Abstract: Aim: The aim of this study was to assess the perception and utilization of HIV services in Lagos Nigeria. Methods: One focus group discussion (FGD) and three key informant interviews (KIIs) were conducted in each of the three LGAs in the state. Results: A high level of awareness of HIV was observed among the participants. However, risk perception was varied with some members of the community refusing to believe that HIV is real and some misconceptions about risk factors. The availability of testing and treatment centers was not well known to a number of the respondents. Stigmatization of those infected is still high due to the perceived high transmissibility of the disease. Conclusion: There is need for the Lagos State government to leverage on all existing health facilities in the state for the provision of HIV testing services and focus efforts on removing misconceptions and stigmatization of those infected with HIV.